Effetto-Vertigo. Il ritratto come genere letterario in prospettiva "cross-temporal" (Comparatismi, 2025)
From a cross-temporal and inter-arts perspective, this proposal considers the role of genre theory, using the “portrait” as a case study. In Felski’s words, through comparative theory, texts can be seen not as “object-to-be-explained” but rather as “fellow actor and cocreator of relations, attitudes, and attachments” (Felski, 2011, p. 589). This research aims to demonstrate that the portrait case study adds valuable data to genre theory, as it is both referential – connected to a real referent, namely the art object – and figural, representing the “intimate” identity of a subject (Felski, 2016, p. 754). The proposal aims to explore the limits of genre classification from transnational and trans-temporal perspectives, considering the theoretical interaction between the verbal and the visual.
Keywords: Literary portraits; Genre theory; Actor-network theory